Letters to Florence O'Donoghue from various individuals (K - L) in response to queries and newspaper advertisements seeking information on Liam Lynch, - O'Donoghue, Florence, 1895-1967 (1941)
Correspondents are Tadg Kearney, James Kelly, Donal Kiely, Jim Killian, James Kirwan, Robert Langford, Siobhán Langford, Tom Laurence, James Leahy and John Lehane.